Nacionalidade circunstancial : o caso dos Macuxi entre o Brasil e a Guiana - Ferreira, Gianne Gomes (2017)
This research addresses the importance of nationality for cross-border indigenous groups, especially the Macuxi, on the Brazil / Guyana border. Explains in more detail the institute of nationality. It shows the peculiarities of the Macooshi as a people one, with their own lifestyle and identity. At the same time, it reveals its sui generis condition of transnationals that it deflagrates in sub-citizenship. It analyzes the problematic and feasibility of extending the ownership of Brazilian nationality to the group modality, for the native peoples, in the human rights scope.